Effects of Emotion on Medical Decisions Involving Tradeoffs. (November 2018) - Ellis, Erin M.; Klein, William M.P.; Orehek, Edward; Ferrer, Rebecca A.
Risk perceptions for a disease can motivate use of medications that reduce disease risk. However, these medications are often accompanied by elevated risks for other adverse health effects, and perceived risk of these side effects may also influence decisions. Emotions experienced at the time of a decision influence risk judgments and decision making, and they may be important to examine in these tradeoff contexts. This study examined the effect of experimentally induced fear and anger on risk perceptions and willingness to use a hypothetical medical treatment that attenuates risk of one condition but increases the risk for another. Participants ( N = 1948) completed an induction of fear, anger, or neutral emotion and then read about a hypothetical medication that reduced risk for one health condition but increased risk for another, and they indicated their willingness to use it. Deliberative, experiential, and affective risk perceptions about both health conditions were measured, conditional on taking and not taking the medication. Fear condition participants were more willing to take the medication than those in the neutral condition (β = 0.14; P = 0.009; 95% confidence interval, 0.036–0.25). Fear also increased deliberative, experiential, and affective risk when conditioned on not using the medication, P s < 0.05. In contrast, anger did not influence willingness to use the medication ( P = 0.22) and increased deliberative and affective risk of side effects when conditioned on using the medication ( P < 0.05). As one of the first studies to examine how emotion influences tradeoff decision making, these findings extend our understanding of how fear and anger influence such decisions.